PRELIMINARY STUDY OF CO-GASIFICATION OF DIFFERENT LIGNOCELLULOSIC BIOMASS IN BENCH SCALE REACTOR - INAYAT, MUDDASSER (2015)
Utilisation of biomass energy for power generation is a cheapest and environmental friendly way via gasification technology. However, challenge with biomass gasification is shortage of feedstock for continuous gasification process which consequently interruption in power generation. Mixing ofdifferent biomass materials improved the physical or morphological behaviour of inferior biomass that reduces the operational instability ofprocess. Co-gasification of different biomass materials would enable flexible utilisation of solid feedstock in order to obtained uniform gas composition for power generation applications. The current research focuses on the co-gasification of different lignocellulosic biomass materials with different blending ratios for the quality of syngas and performance of the process. Furthermore, the temperature profile and syngas flare obtained from different blending ratios of feedstock were studied. Characterization of biomass materials (wood, OPF and coconut shell) mainly consists ofultimate analysis, proximate analysis, heating value and elemental analysis were investigated prior to experiments. The co-gasification study was carried out in a batch feed downdraft gasifier. The syngas composition (CO, H2, CH4 and C02) from each experiment was analyzed using Emerson X-Stream online gas analyzer.